1991
DOI: 10.1002/jcb.240470410
|View full text |Cite
|
Sign up to set email alerts
|

Activating mutations in the NH2‐ and COOH‐terminal moieties of the Gsα subunit have dominant phenotypes and distinguishable kinetics of adenylyl cyclase stimulation

Abstract: The alpha subunit polypeptides of the G proteins Gs and Gi2 stimulate and inhibit adenylyl cyclase, respectively. The alpha s and alpha i2 subunits are 65% homologous in amino acid sequence but have highly conserved GDP/GTP binding domains. Previously, we mapped the functional adenylyl cyclase activation domain to a 122 amino acid region in the COOH-terminal moiety of the alpha s polypeptide (Osawa et al: Cell 63:697-706, 1990). The NH2-terminal half of the alpha s polypeptide encodes domains regulating beta g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…3). Confirming earlier studies on adenylylcyclase in other cells (15,16), expression of G s␣ and G s␣ G225T significantly enhanced cyclic AMP accumulation. Substitution of G s␣ sequence with G i␣2 (1-7) , G i␣2 (1-64) , G i␣2 , and G i␣2 sequences attenuated the enhanced response observed with expression of either G s␣ or G s␣ G225T.…”
Section: Differentiation Of F9 Teratocarcinoma Stem Cellssupporting
confidence: 87%
See 2 more Smart Citations
“…3). Confirming earlier studies on adenylylcyclase in other cells (15,16), expression of G s␣ and G s␣ G225T significantly enhanced cyclic AMP accumulation. Substitution of G s␣ sequence with G i␣2 (1-7) , G i␣2 (1-64) , G i␣2 , and G i␣2 sequences attenuated the enhanced response observed with expression of either G s␣ or G s␣ G225T.…”
Section: Differentiation Of F9 Teratocarcinoma Stem Cellssupporting
confidence: 87%
“…The patterns for cyclic AMP accumulation by clones expressing the various subunits and chimeras were similar for the basal, isoproterenol-stimulated (100 M), and forskolin-stimulated (50 M) conditions.These data demonstrate that, when stably expressed in the context of F9 teratocarcinoma cells, G s␣ stimulates, G i␣2 inhibits, and substitution of G s␣ with increasing N-terminal regions of G i␣2 attenuates activation of adenylylcyclase. Thus, the G-proteins expressed have retained the ability to recognize receptor, bind and exchange GTP, and to activate one known effector, adenylylcyclase, as previously noted (15,16).…”
Section: Differentiation Of F9 Teratocarcinoma Stem Cellsmentioning
confidence: 84%
See 1 more Smart Citation
“…Certain mutations of Gsa subunit, which alter the GTPase cycle, have been shown to be involved in such tumors as pituitary and thyroid tumors, with mutations often occurring at the same 2 critical sites as mentioned above: amino acid residues 201 and 227. These mutations induce a stabilization of Gsa in the active conformation by inhibiting its intrinsic GTPase activity and lead to a constitutive activation of adenylyl cyclase, thereby promoting cell proliferation (20,21). Based on this mechanism, the aberrant splicings with in-frame deletions presented in our study also raise the possibility of potentially oncogenic Gsa subunits de cient in GTPase activity.…”
Section: Discussionmentioning
confidence: 55%
“…2B). Earlier studies have demonstrated that Gs␣-Gi␣2 chimera with these types of substitutions retain their capacity to bind GTP and transduce signaling (17,24).…”
Section: Resultsmentioning
confidence: 99%